2013
DOI: 10.1007/s12031-013-0200-8
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Trauma-Induced Amnesia in Mice by a Thrombin Receptor Antagonist

Abstract: Minimal traumatic brain injury (mTBI) is associated with the existence of retrograde amnesia and microscopic bleeds containing activated coagulation factors. In an mTBI model, we report that thrombin induces amnesia through its receptor protease-activated receptor 1 (PAR-1). Thrombin activity was significantly elevated (32 %, p < 0.05) 5 min following mTBI compared to controls. Amnesia was assessed by the novel object recognition test in mTBI animals and in animals injected intracerebroventricularly (ICV) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 43 publications
4
31
0
1
Order By: Relevance
“…Using rodent models of mTBI and relevant cognitive and biological tests, numerous treatments with mechanism-based drug features have been reported to ameliorate mTBI induced cognitive deficits. As a recent example among many, we have lately shown that an increased thrombin concentration induced by mTBI may cause amnesia through the activation of its receptor, the proteases activated receptor 1 (PAR1) (Itzekson et al, 2014, Maggio et al, 2014); thereby exposing a novel therapeutic target potentially underpinning cognitive detriments of trauma. In the following sections, several widely used rodent models of mTBI are highlighted that can be combined with well characterized behavioral assays, epitomized by the novel object recognition (NOR) task for assessing cognitive deficits, to provide a methodological toolbox for evaluating molecular mechanisms involved in mTBI.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Using rodent models of mTBI and relevant cognitive and biological tests, numerous treatments with mechanism-based drug features have been reported to ameliorate mTBI induced cognitive deficits. As a recent example among many, we have lately shown that an increased thrombin concentration induced by mTBI may cause amnesia through the activation of its receptor, the proteases activated receptor 1 (PAR1) (Itzekson et al, 2014, Maggio et al, 2014); thereby exposing a novel therapeutic target potentially underpinning cognitive detriments of trauma. In the following sections, several widely used rodent models of mTBI are highlighted that can be combined with well characterized behavioral assays, epitomized by the novel object recognition (NOR) task for assessing cognitive deficits, to provide a methodological toolbox for evaluating molecular mechanisms involved in mTBI.…”
Section: Traumatic Brain Injurymentioning
confidence: 99%
“…In synopsis, PAR-1 has a key role in memory formation and synaptic plasticity (Maggio et al, 2013a,b, 2014), which can be regulated in a concentration-dependent manner by thrombin under physiological and pathological conditions. Interestingly, thrombin concentrations rise in the brain just a few minutes following a mTBI (Itzekson et al, 2014; Maggio et al, 2014), with such an increase in concentrations related to a poor NOR performance in animals challenged by brain trauma. Notably, injection of the PAR1 antagonist SCH79797 prevents memory deficit and rescues LTP in injured mice.…”
Section: Pharmaceutical Treatments For Weight Drop-induced Damage mentioning
confidence: 99%
“…The minimal number of animals was used and all efforts were made to minimize suffering. The study was carried out in 8 weeks old male C57BL/6J mice and mTBI was induced using a free weight drop concussive device as previously described (Itzekson et al, 2014). Briefly, the device consisted of an 80-cm high metal tube (13 mm in diameter) placed vertically over the head of the mouse.…”
Section: Experimental Settingmentioning
confidence: 99%
“…Thrombin, a serine protease participating in the coagulation cascade, is originated from prothrombin cleavage by activated factor X (Krishnaswamy, 2013). After binding to its protease activated receptor (PAR1), Thrombin-PAR1 activation leads to NMDA receptors potentiation and massive calcium influx, followed by a glutamate mediated hyperexcitable state, and a lowered threshold for seizure development (Gingrich et al, 2000;Maggio et al, 2008) Critically, thrombin-PAR1 complex also participates in mTBI mechanism, causing in vivo synaptic disfunction and amnesia, effects that were reversed after the administration of thrombin inhibitors (Itzekson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The above studies, along with the novel demonstration of Aβ‐mediated thrombin generation, point to a key role of thrombin and its serpin inhibitors (such as PN‐1) in AD pathology, and to the plausible therapeutic potential of thrombin receptor blockers in treating neurodegenerative disorders . Future studies on AD and additional neurodegenerative diseases should consider thrombin and its brain receptors as tentative drug targets.…”
mentioning
confidence: 98%